1994
DOI: 10.1080/10402009408983365
|View full text |Cite
|
Sign up to set email alerts
|

Misalignment In A Complete Shell Gas Foil Journal Bearing

Abstract: The effect of misalignment on the performance of a completeAn isothermal perfect gas is used as the lubricant fluid. Results are shell gas foil bearing is discussed. An iterative theoretical model presented demonstrating the effect of misalignment on load capacity, based on the finite element method is used. The model includes minimum clearance, and moments acting normal to the journal. membrane and elastic foundation effects in the structural model. KEY WORDS Final manuscript approved September 15, 1992 Foil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…A model that does not include membrane effects will underpredict the maximum load because of contact between the top foil and the journal. Similar effects of membrane strains were discussed by Carpino, et al (22), (23).…”
Section: Resultssupporting
confidence: 53%
“…A model that does not include membrane effects will underpredict the maximum load because of contact between the top foil and the journal. Similar effects of membrane strains were discussed by Carpino, et al (22), (23).…”
Section: Resultssupporting
confidence: 53%
“…[5]- [8] into Eq. [2], neglecting the higherorder terms, it yields the zeroth-order and first-order equations. These equations for perturbation in film thickness due to journal displacement can be expressed in the following non-dimensional form:…”
Section: Perturbationmentioning
confidence: 99%
“…Very little work has been reported on GFB misalignment. Carpino (1994) analyzed misalignment effects and found that load capacity is not affected strongly, but minimum film thickness decreases with increased misalignment. However, those results were for very small angular misalignments (maximum angle equal to C/L radians) relative to those in the present tests (maximum angle of 10.4 C/L radians).…”
Section: Misalignmentmentioning
confidence: 99%